2018
DOI: 10.1002/ajmg.a.38597
|View full text |Cite
|
Sign up to set email alerts
|

Variable immune deficiency related to deletion size in chromosome 22q11.2 deletion syndrome

Abstract: The clinical features of 22q11.2 deletion syndrome include virtually every organ of the body. This review will focus on the immune system and the differences related to deletion breakpoints. A hypoplastic thymus was one of the first features described in this syndrome and low T cell counts, as a consequence of thymic hypoplasia, are the most commonly described immunologic feature. These are most prominently seen in early childhood and can be associated with increased persistence of viruses. Later in life, evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 55 publications
3
51
0
1
Order By: Relevance
“…Smaller deletions bracketed by the other LCRs have overlapping clinical features. We studied the deletion size as a predictor of immune deficiency and found that the deletion of TBX1 was associated with the immunodeficiency . The distal deletions that do not include TBX1 and the duplications appear to be largely spared the immunodeficiency.…”
Section: Genetic Basismentioning
confidence: 99%
See 3 more Smart Citations
“…Smaller deletions bracketed by the other LCRs have overlapping clinical features. We studied the deletion size as a predictor of immune deficiency and found that the deletion of TBX1 was associated with the immunodeficiency . The distal deletions that do not include TBX1 and the duplications appear to be largely spared the immunodeficiency.…”
Section: Genetic Basismentioning
confidence: 99%
“…We therefore examined the association of cardiac anomalies to T cell count in infants with 22q11.2del and found there was no relationship between the complexity of the cardiac anomaly and the T cell count . We also examined deletion size as an independent driver of T cell lymphopenia . Deletion size was not critical but inclusion of the gene TBX1 in the deletion was associated with worse T cell counts.…”
Section: T Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main characteristics observed in this syndrome are dysmorphic facial features, velophrayngeal abnormlaities, conotruncal cardiac defects, immunodeficiency, thymic insufficiency, hypoparthyroidisim, and developmental delays 7 . We hypothesize that having 22q11.2 deletion syndrome would influence the resource utilization in the postoperative period, as these subjects would have a prolonged and more complicated postoperative course given the presence of immunodeficiency and multiple noncardiac anomalies that are associated with 22q11.2 deletion syndrome 8 …”
Section: Introductionmentioning
confidence: 99%